2019
DOI: 10.3390/infrastructures4030039
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Pedestrian Crossing Speed and Waiting Time at Intersections in Dhaka

Abstract: Pedestrian crossing speed and waiting time are critical parameters for designing traffic signals and ensuring pedestrian safety. This study aimed to carry out microscopic level research on pedestrian crossing speed and waiting time at intersections in Dhaka. To fulfill this aim, crossing-related data of 560 pedestrians were collected from three intersections in Dhaka using a videography survey method. Descriptive and statistical analyses were carried out, and then two multiple linear regression (MLR) models we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 34 publications
1
9
0
2
Order By: Relevance
“…Concerning company, crossing speeds were slowing down as the size of the company group was growing (Bansal et al, 2019;Kadali and Vedagiri, 2019;Shaaban, 2019). The same effect was noticed when pedestrians were crossing while holding objects, such as bags or luggage (Zafri et al, 2019). To this end, since the crossing duration expresses the exposure to risks, it is of great importance to further investigate it and particularly to focus on distracted pedestrians who are considered as more vulnerable.…”
Section: Literature Reviewmentioning
confidence: 93%
See 2 more Smart Citations
“…Concerning company, crossing speeds were slowing down as the size of the company group was growing (Bansal et al, 2019;Kadali and Vedagiri, 2019;Shaaban, 2019). The same effect was noticed when pedestrians were crossing while holding objects, such as bags or luggage (Zafri et al, 2019). To this end, since the crossing duration expresses the exposure to risks, it is of great importance to further investigate it and particularly to focus on distracted pedestrians who are considered as more vulnerable.…”
Section: Literature Reviewmentioning
confidence: 93%
“…Based on literature review, crossing speed is affected by the intersection control type, with the relevant results varying between signalized and unsignalized intersections and crossings through midblocks. More specifically, Hassouna (2020) observed that pedestrians cross the unsignalized intersections faster than the signalized ones, while Zafri et al (2019) noticed slower crossing speeds in corresponding cases. Likewise, crossing was associated with gender, age, company group size, pedestrian flow and volume, the carrying of objects and in some cases with the use of a mobile phone.…”
Section: Literature Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…The results highlighted the impact of intersection clearing time on violations and percentage of unsafe crossings that occur. Gender and age are often regarded key factors; crossing time [2] and the waiting time [4] of the pedestrians varied with age and gender. Females waited almost twice the amount of time as males at the crossings [5], and older pedestrians have longer waiting time [6].…”
Section: Introductionmentioning
confidence: 99%
“…Research into collecting and measuring reliable microscopic traffic data is a fundamental aspect in road network planning scientific literature. Several applications can be implemented by using the acquired dataset in terms of traffic safety, road capacity, and level of service analysis [1][2][3][4]. However, as the traffic conditions get more complex, the level of detail and the quality of the collected information is getting higher.…”
Section: Introduction 1microscopic Traffic Data Acquirementmentioning
confidence: 99%